Expression Profile of PmiR-31, Novel npcRNA Of Proteus Mirabilis Under Different Growth Phases and Stress Conditions - Abirami Sanniraj; Suresh V. Chinni; Sumitha Samuggam; Eugene Boon Beng Ong; Veeranjaneya Reddy Lebaka5; Lee Su Yin (Malaysian Journal of Science (MJS), 2025)
Proteus mirabilis (P. mirabilis), known for its swarming motility, is a facultatively anaerobic, rod-shaped, Gram-negative bacterium. It forms extended swarmer cells as well as moves in a bull’s-eye formation. Proteus mirabilis significantly causes catheter-associated urinary tract infections through virulence components including flagella, fimbriae, hemolysin, urease, and proteases. Flagella-related motility allows P. mirabilis to infect the urinary system. The flagellum, composed of about 20 proteins, has a body that penetrates the cell wall, a curved hook, and a filament extending several micrometers. Previously, we knocked out PmiR-137, anticipated to modulate flhDC, which involve in the central transcriptional activator for flagellum formation and performed a differential gene expression study. We discovered npcRNA PmiR-31, expected to influence fliZ production via the TargetRNA web tool. We analyzed PmiR-31 expression under various stress and growth phases via northern blot. The PmiR-31 was highly expressed in stress conditions but not in the mutant strain. Since FliZ regulates flagella assembly, npcRNA PmiR-31 may repress fliZ translation, preventing flagella synthesis and promoting biofilm formation to evade the immune system.